(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2025)
This article aims to study the possibility of applying Restorative Justice practices in processes submitted to the jury trial. Dialectics was used as a method, as well as bibliographic and documentary research. Initially, concepts relating to the jury rite were presented. It then sought to explore theoretical and practical aspects of restorative justice, presenting this as a possible proposal for criminal justice. Finally, we sought a joint analysis of the possibilities and obstacles of restorative justice practices in processes submitted to the jury, especially crimes considered serious. As a conclusion, we have that restorative justice is a possibility in jury processes, and has even been applied in cases in Brazil since 1995. However, there remains a certain resistance from Brazilian courts to the application of a method with widespread dissemination that is still recent, with a view to removing State’s monopoly on punishment